1995
DOI: 10.1074/jbc.270.20.11776
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Dictyostelium Protein Kinase Required for Actin Activation of the Mg2+ATPase Activity of Dictyostelium Myosin ID

Abstract: We have isolated a protein from Dictyostelium with a molecular mass of 110 kDa as judged by SDS-gel electrophoresis that can stimulate the actin-activated MgATPase activity of Dictyostelium myosin ID (MyoD). In the presence of MgATP the 110-kDa protein incorporated phosphate into itself and into the heavy chain, but not the light chain, of MyoD. Phosphorylation to 0.5 mol of Pi/mol increased the MyoD actin-activated MgATPase rate from 0.2 to 3 mumol/min/mg. Renaturation following SDS-gel electrophoresis demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 45 publications
5
57
0
Order By: Relevance
“…PakB with an N-terminal FLAG-tag displayed a similar distribution to endogenous PakB when expressed in PakB-null cells ( Figure 3B). The relatively weak cortical distribution of PakB is consistent with protein purification and quantitative immunoblotting studies that show that PakB is predominately a cytosolic protein (Lee and Côté, 1995;Senda et al, 2001). …”
Section: Full-length Pakb Localizes To the Leading Edge Of Migrating supporting
confidence: 51%
See 1 more Smart Citation
“…PakB with an N-terminal FLAG-tag displayed a similar distribution to endogenous PakB when expressed in PakB-null cells ( Figure 3B). The relatively weak cortical distribution of PakB is consistent with protein purification and quantitative immunoblotting studies that show that PakB is predominately a cytosolic protein (Lee and Côté, 1995;Senda et al, 2001). …”
Section: Full-length Pakb Localizes To the Leading Edge Of Migrating supporting
confidence: 51%
“…These authors conclude that PakA, which localizes to the posterior of migrating cells, functions to promote the assembly of myosin II into bipolar filaments. In a second study, PakA-null cells were found to display no detectable defects with respect to locomotion or cytokinesis (Muller-Taubenberger et al, 2002).PakB was initially identified through its ability to phosphorylate and activate MyoD, a single-headed type I myosin (Lee and Côté, 1995;Lee et al, 1996). PakB was originally called myosin I heavy chain kinase, but it has been renamed to conform to the gene name (pakB) (Fey et al, 2004).…”
mentioning
confidence: 99%
“…Importantly, MYOA is one of a small subset of myosins (class I myosins of A. nidulans, Acanthamoeba castellanii, Dictyostelium discoideum, Saccharomyces cerevisiae, Schizosaccharomyces pombe, and the eight class VI myosins that have been sequenced) that have either a serine or threonine residue in the motor domain at a position [the TEDS site (10), Ser-371 in MYOA] in an actinbinding surface loop (11) where all other myosins contain either an aspartate or glutamate residue (10,12,13). The actindependent MgATPase and in vitro motility activities of A. castellanii (14) and D. discoideum (15) class I myosins are regulated by phosphorylation of the TEDS-site serine or threonine by p21-activated kinases (16,17). Replacement of the TEDS-site serine of A. castellanii myosin IC by glutamate or alanine (18) mimics, in vitro, the phosphorylated (active) and unphosphorylated (inactive) states, respectively.…”
mentioning
confidence: 99%
“…As was previously shown for Acanthamoeba myosin Is, evidence is accumulating that phosphorylation is essential for full activity of their actin-activated ATPase (43,78). Correspondingly, a close homolog of Acanthamoeba myosin I heavy chain kinase (MIHCK), a kinase of the PAK/Ste20 family, has been cloned in D. discoideum and is active on MyoD (44,79). Soldati, Geissler, and Schwarz identification of IQ motifs in every D. discoideum myosin I except MyoK, direct evidence is still lacking for a direct binding of calmodulin to their neck domains.…”
Section: Regulationmentioning
confidence: 88%